A study on the influence of product environmental information transparency on online consumers’ purchasing behavior of green agricultural products - Fu, Shaoling; Ma, Ruili; He, Guangyao; Chen, Zhiyi; Liu, Hua (Frontiers in Psychology, 2023)
Introduction In 2020, the outbreak of COVID-19 has forced consumers to shift their consumption patterns online. However, the problem of online fraud in green agricultural products seriously undermines consumer trust and is detrimental to the sustainable consumption of green agricultural products. Therefore, it is particularly important to enhance consumers’ trust in online sellers. This study aims to investigate how the product environmental information transparency(soil information transparency and water information transparency) affects online consumers’ purchasing behavior of green agricultural products. Methods This study constructs a theoretical framework of “product environmental information transparency - online consumer trust - online purchase behavior”.We conducted an online randomized questionnaire to collect data from a sample of 512 consumers who had experience buying green agricultural products online fitted a structural equation model (SEM). Results The results show that (1) the two dimensions of product environmental information transparency have different effects on different dimensions of online consumer trust. Among them, soil information transparency has a significant positive effect on competence trust, while it does not have a significant positive effect on benevolence trust. Water information transparency has a significant positive effect on both dimensions of online consumer trust, (2) online consumer trust has a significant positive effect on online consumer purchase behavior, and (3) competence trust has a significant positive effect on benevolence trust. Discussion Our study shows that consumer trust in merchants is significantly enhanced by increasing the transparency of environmental information about green agricultural products. different dimensions of environmental information transparency have different effects on different dimensions of online consumer trust. Product information transparency is proposed as a tool for producers to use in the online marketing of green agricultural products. Consumers’ access to information can be improved through online public disclosure of environmental quality indicators in the production process of green agricultural products, and ultimately enhance online consumption of green agricultural products.